Granular activated carbon enhances volatile fatty acid production in the anaerobic fermentation of garden wastes - Chen, Wenwen; Zeng, Yiwei; Liu, Huanying; Sun, Dezhi; Liu, Xinying; Xu, Haiyu; Wu, Hongbin; Qiu, Bin; Dang, Yan (Frontiers in Bioengineering and Biotechnology, 2023)
Garden waste, one type of the lignocellulosic biomass, holds significant potential for the production of volatile fatty acids (VFAs) through anaerobic fermentation. However, the hydrolysis efficiency of garden waste is limited by the inherent recalcitrance and further influences the VFAs production. Granular activated carbon (GAC) could promote the hydrolysis and acidogenesis efficiency during anaerobic fermentation. This study developed a strategy to use GAC to enhance anaerobic fermentation of garden waste without any complex pretreatments and extra enzymes. The results showed that GAC addition could improve VFAs production, especially acetate and reach the maximum total VFAs yield of 191.55 mg/g VSadded, which increased by 27.35% compared to the control group. The highest VFAs/sCOD of 70.01% was attained in the GAC-amended group, whereas the control group only reached 49.35%, indicating a better hydrolysis and acidogenesis capacity attributed to the addition of GAC. Microbial community results revealed that GAC addition promoted the enrichment of Caproiciproducens and Clostridium, crucial for anaerobic VFAs production. In addition, only the GAC-amended group showed the presence of Sphaerochaeta and Oscillibacter genera, which are associated with electron transfer processes. Metagenomics analysis indicated that GAC addition improved the abundance of glycoside hydrolases (GHs) and key functional enzymes related to hydrolysis and acidogenesis. Furthermore, the assessment of major genera influencing functional genes in both groups indicated that Sphaerochaeta, Clostridium, and Caproicibacter were the primary contributors to upregulated genes. These findings underscore the significance of employing GAC to enhance the anaerobic fermentation of garden waste, offering a promising approach for sustainable biomass conversion and VFAs production.